Implementação de Políticas Públicas: a visão dos agentes implementadores do Programa Novo Mais Educação e os fatores de influência na sua atuação com as atividades esportivas. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Considering the studies on the public policies implementation, particularly the bottom-up analytical tendency, we highlight the researches on their implementing agents, namely, street-level bureaucracy and middle-level bureaucracy. Thus, we found a gap of works on implementing agents in contexts of the use of sports and leisure activities to increase the length of permanence of children and adolescents in schools. With this work, we sought to identify the elements of influence on the performance of the implementing agents of sport and leisure in the Novo Mais Educação Program in Ponta Grossa - Paraná. To this purpose, we used the case study research approach, triangulating the collection of bibliographic data, collection of documentary data and questionnaires with the implementing agents. For the analysis of the questionnaires, we used the Iramuteq software and its descending hierarchical classification and word cloud tools. Thus, we identified in the implementing agent’s speeches the presence of individual, institutional and relational factors. However, in the facilitator’s speeches, it was possible to identify the centrality of the institutional factor’s influence, especially the infrastructure element, and the absence of individual and relational factors. This allows us to conclude that, unlike the studies of implementing agents, in which it is possible to perceive the presence of the three factors mentioned, in the study of implementing agents that sports activities, there is a primacy of the institutional factor’s influence, especially the infrastructure element acting in the day-to-day implementation.
Keywords: Implementação; Burocratas de Nível de Rua; Burocratas de Médio Escalão; Escolas de Tempo Integral; Esporte; Implementation; Street-Level Bureaucracy; Mid-Level Bureaucracy; Full-time Schools; Sport; CNPQ::CIENCIAS SOCIAIS APLICADAS